Adsorption and leaching characteristics of ammonium and nitrate from paddy soil as affected by biochar amendment - Rujie Lv; Yong Wang; Xiuxia Yang; Yangping Wen; Xueming Tan; Yongjun Zeng; Qingyin Shang (Plant, Soil and Environment, 2021)
Biochar plays a key role in nitrogen cycling, potentially affecting nitrogen adsorption and leaching when applied to soils. The laboratory experiments were conducted to investigate the adsorption characteristics of rice straw biochar (RSBC) to ammonium (NH4+) and nitrate (NO3-) and the influence of RSBC on leaching characteristics of NH4+ and NO3- at different soil depths using multi-layered soil columns. The results showed that the adsorption characteristics were significantly fitted with Freundlich and Langmuir adsorption isothermal curve models. The Freundlich isotherm model indicated that RSBC has relatively higher adsorption capacity and adsorption intensity to NH4+ than NO3-. Moreover, the Langmuir isotherm model showed that the maximum adsorption capacity of RSBC to NH4+ and NO3- were 31.25 and 10.00 mg/g, respectively. The leaching experiments showed that the contents of NH4+ in the leachates from the soil columns showed significant differences at different depths depending on the application amount of RSBC. Compared with CK (0% RSBC amendment), the overall cumulative losses of NH4+ via leaching were decreased by 23.3, 35.1 and 13.7% after adding 2, 4 and 6% RSBC, respectively. Correspondingly, the contents of residual soil NH4+ in the soil column were increased significantly with the RSBC amendment at different depths. However, the losses of NO3- via leaching from the soil columns could not be retarded obviously by RSBC. Therefore, the application of an appropriate biochar rate is beneficial to retard the losses of soil NH4+ from paddy soil.